The analysis of the key drivers and barriers of cloud migration in companies in Bosnia and Herzegovina - Kasim Tatić; Zijad Džafić; Mahir Haračić; Merima Haračić (Economic Review: Journal of Economics and Business, 2020)
The effective use of cloud technology eliminates the barriers and potential IT obstacles that companies face by using a traditional way of developing a platform for the information systems, as a backbone of modern business. Practical application of any technology and innovation produces distinct advantages and risks that need to be carefully analyzed, identified, and managed within the company. Cloud technology will perform an increasing role in the future (primarily in developing countries) because it will be effective to combat certain problems that cause inefficiencies that threaten company's com- petitiveness, operational flexibility, and thus its existence. The research was conducted between February and September, 2019 in the form of online research. The re- search was sent to 387 participants, but in total 84 questionnaires were filled in full. According to the re- search results, the respondents believe the key drivers of cloud migration comprise the following: improving effi- ciency, enabling more extensive data sharing capabilities, improving security, increasing innovations, reducing costs. The aforementioned research results are correlated with studies conducted by other authors over different time periods. According to the research results, the most significant obstacles of cloud migration include the fo- llowing: lack of internal experts, privacy, lack of respo- nsibility of cloud providers in case of security incident, costs and complexity of migration to the cloud, etc. The research results point to the conclusion that the use of cloud technology increases the degree of agility, opera- tional flexibility, economic productivity, and competiti- veness of companies. An increase in the level of cloud awareness as well as in the education of top managers, with simultaneous internal and external changes within the company, would consequently result in the increase of cloud migration in domestic companies.
Keywords: L26; C38; 330; cloud computing drivers and barriers; productivity; agility; efficiency